A Combined Use of Rhizobacteria and Moringa Leaf Extract Mitigates the Adverse Effects of Drought Stress in Wheat (Triticum aestivum L.) - Lalarukh, Irfana; Al-Dhumri, Sami A.; Al-Ani, Laith Khalil Tawfeeq; Hussain, Rashid; Al Mutairi, Khalid Awadh; Mansoora, Nida; Amjad, Syeda Fasiha; Abbas, Mohamed H. H.; Abdelhafez, Ahmed A.; Poczai, Peter; Meena, Khem Raj; Galal, Tarek M. (Frontiers in Microbiology, 2022)
Less nutrient availability and drought stress are some serious concerns of agriculture. Both biotic and abiotic stress factors have the potential to limit the crop productivity. However, several organic extracts obtained from moringa leaves may induce immunity in plants under nutritional and drought stress for increasing their survival. Additionally, some rhizobacterial strains have the ability to enhance root growth for better nutrient and water uptake in stress conditions. In order to cover knowledge gap of interactive effects of beneficial rhizobacteria and moringa leaf extracts, present study is conducted. The aim of current experimental study is to investigate the effectiveness of sole and combined used of rhizobacteria and moringa leaves extracts against nutritional and drought stress in wheat. Nitrogen fixing bacteria Pseudomonas aeruginosa (Pa) (108 cfu mL−1) was inoculated to wheat plants with and without foliar applied moringa leaf extracts at two different concentrations (MLE 1= 1:15 v/v and MLE 2= 1:30 v/v) twice at 25 and 35 days after seed sowing (50 mL per plant) after the establishment of drought stress. Results revealed that Pa+MLE 2 significantly increased fresh weight (FW), dry weight (DW), lengths of roots and shoot and photosynthetic contents of wheat. A significant enhancement in total soluble sugars, total soluble proteins, calcium, potassium, phosphate and nitrate contents validated the efficacious effect of Pa+MLE 2 over control treated plants. Significant decrease in sodium, proline, glycine betaine, electrolyte leakage, malondialdehyde, hydrogen peroxide, superoxide dismutase (SOD) and peroxide (POD) concentrations in wheat cultivated under drought stress conditions also represents imperative role of Pa+MLE 2 over control. In conclusion, Pa+MLE 2 can alleviate nutritional stress and drought effects in wheat. More research in this field is required to proclaim Pa+MLE 2 as most effective amendment against drought stress in distinct agro-ecological zones, different soil types and contrasting wheat cultivars worldwide.